MAKNA DAN HAKIKAT WASATHIYAH - Husna, Nurul (Transpublika Publisher, 2021)
The concept of Islamic Wasathiyah or Islamic moderation has now become a direction or school of Islamic thought that has become a meaningful discourse in the Islamic world, considering the condition of Muslims who are always accused in every incident of violence committed by Muslim individuals who do not control their personality and this is Islamic teaching. Wasathiyyah has the meaning of the best thing or a noble thing, meaning that Islamic wasathiyyah teachings are the best teachings, because they follow the currents and developments of the times by carrying out according to existing sharia law. The goal: to find out more about wasathiyah, to find out the urgency faced by wasathiyah, to find out the benefits of wasathiyah. Method: descriptive. The meaning of wasathiyah is a basic religious attitude that has a strong meaning and is stated in the verse of the Koran about the wasathan ummah. between nations